Artistic Labor and the Production of Value: An Attempt at a Marxist Interpretation. Issue 2 (2nd April 2016) - Durán, José María
Abstract : This essay addresses the production of value while considering the artistic labor process, with a focus on the visual arts. First, the commodity form of artistic works is examined and theoretical challenges are pointed out. Second, a specific ideology of the artistic labor process is considered. This ideology serves to conceal the economic relations of production that shape artistic labor as a producer of value. Finally, an analysis of the substance of value is proposed. Intellectual property rights are examined from the perspective of value production.